The Effects of Terrorism and War on the Oil and Prices Stock Indices Relationship - Christos Kollias; Catherine Kyrtsou; Stephanos Papadamou (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
This paper, investigates the effect war and terrorism, have on the covariance between oil prices and the indices of four major stock markets - the American S&P500 and the European DAX, CAC40 and FTSE100 - using nonlinear BEKK-GARCH type models. Findings reported herein indicate that the covariance between stock and oil returns is affected by war. A tentative explanation is that the two wars examined here, predispose investors and market agents for more profound and longer lasting effects. On the other hand, in the case of terrorist incidents that, vis-à-vis war, are of a more transitory nature and one-off security shocks, only the co-movement between CAC40, DAX and oil returns is affected. No significant impact for the same terrorist events is observed in the relationship between the S&P500, FTSE100 and oil returns. This difference in the reaction may tentatively be interpreted as indicating that the latter markets are more efficient in absorbing the impact of terrorist attacks.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: G10; E0; C5; 330; war; terrorism; crude oil; stock market returns; co-movement